The promise of the bell - Repplier, Agnes, 1855-1950; Adams, John Wolcott, 1874-1925 (Salt Lake City, UT : Project Gutenberg, 2025)
"The Promise of the Bell: Christmas in Philadelphia" by Agnes Repplier is a reflective historical account written in the early 20th century. The book explores the significance of Christmas traditions and social customs in Philadelphia, intertwining the celebration of the holiday with the legacy of the Liberty Bell and the values of life, liberty, and the pursuit of happiness. Repplier captures the essence of a city rich in history and camaraderie, conveying how festive gatherings foster a sense of community. In the narrative, Repplier delves into the interplay between social gatherings, celebration, and the pursuit of genuine happiness among Philadelphians. She illustrates the city's evolution from its historical roots to the present day, highlighting the communal celebrations during Christmas$1 (Bsuch as caroling and shared meals$1 (Bthat knit together the fabric of society. Through vivid descriptions of gatherings, traditions, and the poignant symbolism of the Liberty Bell, Repplier reflects on the changes that have occurred in societal values over time, while maintaining an optimistic view of the enduring spirit of goodwill and friendship among residents. Her insight into the past imbues the Christmas season with a sense of nostalgia and warmth, suggesting that even amidst modern challenges, the fundamental promise of the bell endures. (This is an automatically generated summary.)s
Release date is 2025-01-26
Bob Taylor and The Online Distributed Proofreading Team at https://www.pgdp.net (This book was produced from images made available by the HathiTrust Digital Library.)
Keywords: Christmas; Philadelphia (Pa.) -- Social life and customs